Designing Application-based News Text Teaching Materials Integrated with 4C Skills - Ragilia Nurul Fadlilah; Cahyo Hasanudin; Sutrimah (IKIP PGRI Bojonegoro, 2026)
News text learning in schools generally still uses conventional teaching materials that do not fully support the demands of 21st-century education. This study aims to design application-based news text teaching materials integrated with 4C (critical thinking, creativity, communication, and collaboration) skills for seventh-grade junior high school students. The research uses the Research and Development (R&D) method with the ADDIE model which includes the Analyze, Design, Development, Implementation, and Evaluation stages. The research participants were seventh-grade students of SMP Negeri 1 Kenduruan, SMP Negeri 2 Jatirogo, and SMP Negeri 1 Senori. Data were collected through a needs analysis questionnaire, expert validation sheets, and news text writing tests. The results of the study showed that the teaching materials developed obtained a feasibility level of 80% from material experts and 92.5% from media experts. The implementation test showed that the calculated t-value (39.7695) was greater than the critical t-value (1.99601), while the N-Gain value of 0.691165 was in the medium category. Therefore, the designed teaching materials were found to be both feasible and effective to improve students' ability to write news texts.